Sistem Pakar Deteksi Dini Penyakit Stroke Menggunakan Metode Naive Bayes-Certainty Factor - Renaldy Senna Hutama; Nurul Hidayat; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Stroke became one of the diseases that have a high mortality rate in Indonesia and also in the world. It can be dangerous if it is not handled quickly because of a sudden disruption of blood that supplies the brain and if not handled quickly can cause permanent disability or death. In Indonesia, stroke disease in recent years has increased, but the government still has no solution in solving the disease problem. Though the process of handling stroke disease takes sufficient time in detection, if not handled quickly can lead to disability or even death. With the existence of these problems then required a system that can accelerate and simplify the detection of risk to reduce the number of people suffering from stroke. The method used in the detection process is Naive Bayes-Certainty Factor. The Naive Bayes method is used to look for an opportunity to appear from the risk of stroke. For certainty factor method is used to find the value of his belief. This system is built with android based with Java programming language. For the test is done by doing a comparison of detection results from experts with the results of detection conducted by the system where from 25 test data obtained obtained accuracy of 84%.